Single lead atrial synchronised pacing in patients with cardiogenic shock after acute myocardial infarction. Issue 6 (June 1984) - Fowler, M B; Crick, J C; Tayler, D I; English, M J; Woollons, D J; Timmis, A D; Vincent, R; Chamberlain, D A
Abstract : A pacing system requiring only a single lead was used to establish atrial synchronised pacing in eight patients with complete atrioventricular block and cardiogenic shock following acute myocardial infarction. Spontaneous atrial activity was sensed through electrodes positioned on the pacing lead and used to trigger ventricular demand pacing. A normal atrioventricular relation could be established in each of these critically ill patients without the complexity of inserting and finding a stable position for an additional atrial sensing lead. Atrial synchronised pacing at the spontaneous sinus rate had distinct haemodynamic advantages compared with conventional ventricular pacing at 100 beats/min. Mean cardiac output for the group was 3.3 1/min with atrial synchronised pacing compared with 2.6 1/min with conventional pacing, a significant difference of 27%. Peak systolic pressure averaged respectively 91 and 73 mm Hg in the two pacing modes. With conventional ventricular pacing a pronounced phasic alteration in blood pressure was observed, dependent on the altering relation of the paced beats to spontaneous atrial activity. Atrial synchronised pacing abolished this effect and resulted in a stable blood pressure at or above the peak pressure achieved with conventional pacing. Atrial synchronised pacing with a single lead system can be established rapidly. This mode of pacing has appreciable and significant haemodynamic superiority over conventional ventricular pacing in patients with cardiogenic shock and atrioventricular block following acute myocardial infarction.